Pancreatic Cancer Chemotherapy Is Potentiated by Induction of Tertiary Lymphoid Structures in MiceSummary - Francesca R. Delvecchio; Rachel E.A. Fincham; Sarah Spear; Andrew Clear; Marina Roy-Luzarraga; Frances R. Balkwill; John G. Gribben; Michele Bombardieri; Kairbaan Hodivala-Dilke; Melania Capasso; Hemant M. Kocher (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Background and aims: The presence of tertiary lymphoid structures (TLSs) may confer survival benefit to patients with pancreatic ductal adenocarcinoma (PDAC), in an otherwise immunologically inert malignancy. Yet, the precise role in PDAC has not been elucidated. Here, we aim to investigate the structure and role of TLSs in human and murine pancreatic cancer. Methods: Multicolor immunofluorescence and immunohistochemistry were used to fully characterize TLSs in human and murine (transgenic [KPC (KrasG12D, p53R172H, Pdx-1-Cre)] and orthotopic) pancreatic cancer. An orthotopic murine model was developed to study the development of TLSs and the effect of the combined chemotherapy and immunotherapy on tumor growth. Results: Mature, functional TLSs are not ubiquitous in human PDAC and KPC murine cancers and are absent in the orthotopic murine model. TLS formation can be induced in the orthotopic model of PDAC after intratumoral injection of lymphoid chemokines (CXCL13/CCL21). Coadministration of systemic chemotherapy (gemcitabine) and intratumoral lymphoid chemokines into orthotopic tumors altered immune cell infiltration ,facilitating TLS induction and potentiating antitumor activity of chemotherapy. This resulted in significant tumor reduction, an effect not achieved by either treatment alone. Antitumor activity seen after TLS induction is associated with B cell-mediated dendritic cell activation. Conclusions: This study provides supportive evidence that TLS induction may potentiate the antitumor activity of chemotherapy in a murine model of PDAC. A detailed understanding of TLS kinetics and their induction, owing to multiple host and tumor factors, may help design personalized therapies harnessing the potential of immune-oncology.